The effect of future self-continuity on intertemporal decision making: a mediated moderating model - Yang, Ying; Zhang, Liangxiangwan; Qu, Weiguo; Fan, Wei (Frontiers in Psychology, 2024)
Intertemporal decision making refers to the behavior of making decisions after weighing the costs and benefits of two or more outcomes at different time points. This study explores the moderating effect of self-concept clarity on the influence of future self-continuity on intertemporal decision-making and the mediating effect of future outcome consideration, aiming to establish a mediated moderating model. In Study 1, we recruited 370 participants via questionnaire to explore the relationship between future self-continuity and intertemporal decision-making, as well as the moderating effect of self-concept clarity. The results showed that:(1) Future self-continuity significantly negatively predicted the time discount rate of intertemporal decision-making. (2) Self-concept clarity significantly negatively moderated the relationship between future self-continuity and the time discount rate of intertemporal decision-making. In Study 2, we recruited 234 participants using an experimental method and divided them into high and low future self-continuity groups to explore the mediating effect of future outcome 2 consideration and the moderating role of self-concept clarity in the influence of future selfcontinuity on intertemporal decision-making. The results indicated that: (1) Self-concept clarity significantly negatively moderated the impact of future self-continuity on future outcome consideration. ( 2) Future outcome consideration mediated the moderating effect of self-concept clarity on the influence of future self-continuity on intertemporal decision-making. The findings indicated that future self-continuity negatively impacted the time discount rate in intertemporal decision-making. Furthermore, self-concept clarity could indirectly regulate the effect of future self-continuity on intertemporal decision-making through future outcome consideration. These two studies contribute to a better understanding of intertemporal decision-making behavior in different states, help reduce cognitive bias through rational analysis of current states, achieve maximum life benefits, and enrich empirical research in the fields of future self-continuity and intertemporal decision-making.